Voltage injection switching inductor (VISI) method for fast transient response in switch mode power supplies - Jegandren, J.; Gobbi, R.; Athab, Hussain S. (2008)
A fast transient response to a step load change is very essential in a switch mode power supply. The transient response can be improved by means of feedback control method. There are two feedback control methods widely used for SMPS, they are voltage mode control (VMC) and peak current mode control (PCMC). A simulation study on these feedback control methods has been done using Matlab/Simulink. It is found that the PCMC helps the SMPS for a faster transient response compared to the VMC. However, there are a few disadvantages of the PCMC which make it not possible for further transient response improvement. Hence, in this paper a novel feedback control technique is presented and it is called voltage injection switching inductor (VISI). This feedback control method provides a better transient response compared to PCMC. Detailed explanations of the novel method and simulation results are presented in this paper. The simulation results show improvement in terms of fast transient response.